CUSTOMER ATTITUDE AND INTENTION TOWARD SHARIA-COMPLIANT HOTELS - Titin Vegirawati; Yusnaini Yusnaini; Endang Kusdiah Ningsih (Journal of Islamic Monetary Economics and Finance, 2019)
The purpose of this study is to investigate the effect of customer’s attitudes on costumer intention towards sharia compliant hotel. This hotel arranged to serve customers creatively, based on sharia principles. The dimensions of the customer attitudes variable are customer attitudes of hotel operating, hotel design and hotel finance. This study applied convenience sampling to choose the members of samples. 183 hotel costumers were collected to be respondents. Data used is primary data. These data is collected by distributing questionnaires. This study applied partial least square to analyze data. Partial least square appropriate for small size sample. It also appropriate for communication and behavior research. The results of the study shows that customer attitudes of hotel operating, hotel design and hotel finance influenced customer intentions towards sharia compliant hotel positively and significantly. This moderate effect of customers attitude to their intention indicated that there are other factors that might affect customers intention such as price and hotel position.